Step * 1 2 1 of Lemma increasing-sequence-converges


1. : ℕ ⟶ ℝ
2. ∀n:ℕ((x n) < (x (n 1)))
3. {2...}
4. : ℕ+
5. : ℝ
6. (r(c) v/r(c 1)) ≤ (r1/r(M))
7. ∀n:ℕ+(((x (n 1)) n) ≤ ((r1/r(c^n)) v))
8. r0 < v
⊢ n↓ as n→∞
BY
Assert ⌜∀d:ℕ. ∀n,m:ℕ+.  (|n m| <  (|(x n) m| ≤ (r(c) v/r((c 1) c^imin(n;m)))))⌝⋅ }

1
.....assertion..... 
1. : ℕ ⟶ ℝ
2. ∀n:ℕ((x n) < (x (n 1)))
3. {2...}
4. : ℕ+
5. : ℝ
6. (r(c) v/r(c 1)) ≤ (r1/r(M))
7. ∀n:ℕ+(((x (n 1)) n) ≤ ((r1/r(c^n)) v))
8. r0 < v
⊢ ∀d:ℕ. ∀n,m:ℕ+.  (|n m| <  (|(x n) m| ≤ (r(c) v/r((c 1) c^imin(n;m)))))

2
1. : ℕ ⟶ ℝ
2. ∀n:ℕ((x n) < (x (n 1)))
3. {2...}
4. : ℕ+
5. : ℝ
6. (r(c) v/r(c 1)) ≤ (r1/r(M))
7. ∀n:ℕ+(((x (n 1)) n) ≤ ((r1/r(c^n)) v))
8. r0 < v
9. ∀d:ℕ. ∀n,m:ℕ+.  (|n m| <  (|(x n) m| ≤ (r(c) v/r((c 1) c^imin(n;m)))))
⊢ n↓ as n→∞


Latex:


Latex:

1.  x  :  \mBbbN{}  {}\mrightarrow{}  \mBbbR{}
2.  \mforall{}n:\mBbbN{}.  ((x  n)  <  (x  (n  +  1)))
3.  c  :  \{2...\}
4.  M  :  \mBbbN{}\msupplus{}
5.  v  :  \mBbbR{}
6.  (r(c)  *  v/r(c  -  1))  \mleq{}  (r1/r(M))
7.  \mforall{}n:\mBbbN{}\msupplus{}.  (((x  (n  +  1))  -  x  n)  \mleq{}  ((r1/r(c\^{}n))  *  v))
8.  r0  <  v
\mvdash{}  x  n\mdownarrow{}  as  n\mrightarrow{}\minfty{}


By


Latex:
Assert  \mkleeneopen{}\mforall{}d:\mBbbN{}.  \mforall{}n,m:\mBbbN{}\msupplus{}.    (|n  -  m|  <  d  {}\mRightarrow{}  (|(x  n)  -  x  m|  \mleq{}  (r(c)  *  v/r((c  -  1)  *  c\^{}imin(n;m)))))\mkleeneclose{}\mcdot{}




Home Index